Mechanical Strength Analysis of Composite Boards Made from Sengon Buto (Enterolobium Cyclorobium) - Anas Mukhtar; Gatut Rubiono (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
The amount of sawdust in sengon is abundant, so it is necessary to reduce the proportion of sawdust in sengon. This research aims to utilize sawdust and bark of buto sengon. The research was carried out experimentally, where variations in particle size were mixed with adhesive and given a pressure of 1 ton. Mechanical test is carried out by giving a loading of 50; 100; and 150 grams. The test results show that the use of sengon bark powder provides a better load-bearing ability than sengon stems.